Coeval Dancefutures in the Nordics: Dance-as-Art after the Decolonial Turn - Fiksdal, Ingri Midgard (Nordic Theatre Studies, 2023)
This paper looks at the conceptual boundaries of dance-as-art in the Nordics and discusses strategies towards coeval dancefutures away from contemporaneity as a colonial idea(l) of time. The future of dance-as-art in the Nordics needs to be pluralised for the artform to be representative of the regional demography and, as such, stay relevant. This paper proposes two research strands that can contribute to this pluralisation. The first investigates how the conceptual boundaries of dance-as-art shape the leading dance education courses in the Nordics in terms of curricula and student mass, and how these could be expanded. The second strand focuses on diversifying the professional field through artistic research in choreography as a format of speculative future fiction that can suggest new, coeval dancefutures. Dance-as-art is frequently equated with the genre referred to as Contemporary Dance, a highly contradictory term. Rather than denoting all dance forms of the present, it commonly implies a specific set of formalized dance techniques and choreographic formats derived from Western-European and North American modern dance of the twentieth century. Contemporary Dance holds a somewhat exclusive access to formal dance education, art funding as well as networks of dissemination and distribution in the Nordics. Other dance forms are often met with a denial of coeavalness by the Contemporary Dance field, hence largely excluded from the realm of art. This paper argues for the creation of structures for a large variety of coeval dancefutures through revising professional and ethical standards in the Nordic dance field. Instead of continuing to claim the defining power of what constitutes dance-as-art, those of us who currently do have access to education, funding, and dissemination need to take responsibility for challenging and expanding these systems to create a diverse, cultural sustainability within dance-as-art.